1993
DOI: 10.1002/jnr.490350404
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for activation of astrocytes via reactive microglial cells following hypoglossal nerve transection

Abstract: Following peripheral nerve injury, resident microglial cells proliferate and astrocytes undergo hypertrophy, as evidenced, e.g., by an increase in the levels of glial fibrillary acidic protein (GFAP). In a previous study we have shown that infusion of cytosine arabinoside (ARA-C) into the rat brain blocks the axotomy-induced proliferation of microglial cells. This experimental approach has been used in the present study in order to explore the issue of whether the reactive microglial cells are mediators of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 29 publications
1
31
1
Order By: Relevance
“…The increase in the number of microglia/macrophages is a primary event to induce activation of astrocytes. It has been shown that reduction of in the number of microglia/macrophages leads to attenuation of astrocytic activation (Giulian et al, 1989;Svensson et al, 1993). In the present study, the stub wound increased the number of microglia/macrophages, which was revealed by a staining of GSA-I B 4 (Marty et al, 1991), though which effect was not affected by BQ788 and FR139317 (Table 2).…”
Section: Introductioncontrasting
confidence: 59%
“…The increase in the number of microglia/macrophages is a primary event to induce activation of astrocytes. It has been shown that reduction of in the number of microglia/macrophages leads to attenuation of astrocytic activation (Giulian et al, 1989;Svensson et al, 1993). In the present study, the stub wound increased the number of microglia/macrophages, which was revealed by a staining of GSA-I B 4 (Marty et al, 1991), though which effect was not affected by BQ788 and FR139317 (Table 2).…”
Section: Introductioncontrasting
confidence: 59%
“…Since microglia are activated and replicate earlier than astrocytes, cytokines released by activated microglia may contribute to the hypertrophy and hyperplasia of neighboring astrocytes. This suggestion is strongly supported by the finding that inhibition of microglial proliferation following hypoglossal axotomy also prevents increases in GFAF' immunostaining and GFAP mRNA (Svensson, et al, 1993).…”
Section: Proliferating Astrocytes: Source and Fatementioning
confidence: 79%
“…Cell Activation-It is well known that peripheral nerve injury induces glial cell activation in the spinal cord (35)(36)(37). The activation of microglia and astrocytes in the nerve-damaged mice was tested by immunostaining with anti-CD11b and anti-GFAP antibodies, respectively.…”
Section: Tlr2 Is Required For the Nerve Injury-induced Spinal Cord Glialmentioning
confidence: 99%